Get detailed and accurate responses to your questions on IDNLearn.com. Our platform is designed to provide reliable and thorough answers to all your questions, no matter the topic.
Sagot :
Answer:
[tex]\sf x^2+y^2=37[/tex]
Step-by-step explanation:
Equation of a circle: [tex]\sf(x-h)^2+(y-k)^2=r^2[/tex]
where (h, k) is the center and r is the radius
Given the center is at (0, 0)
[tex]\sf \implies (x-0)^2+(y-0)^2=r^2[/tex]
[tex]\sf \implies x^2+y^2=r^2[/tex]
Given the circle passes through point (1, -6):
[tex]\sf \implies (1)^2+(-6)^2=r^2[/tex]
[tex]\sf \implies r^2=37[/tex]
Therefore, the equation of the circle is:
[tex]\sf \implies x^2+y^2=37[/tex]
Equation of a circle passing through origin
- x²+y²=r²
So
As (1,-6) lies on circle it will satisfy
- 1²+(-6)²=r^2
- 1+36=r²
- r²=37
Now
equation of the circle
- x²+y²=37
Your engagement is important to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. For dependable and accurate answers, visit IDNLearn.com. Thanks for visiting, and see you next time for more helpful information.